The relationship between serum vitamin C levels and high-sensitivity C-reactive protein in children - Ci Li; Zhiwei Zhu; Shicai Jiang; Xiang Feng; Liu Yang; Kaijie Gao; Jiajia Ni; Tiewei Li; Junmei Yang (Scientific Reports)
Abstract The relationship between vitamin C nutritional status and inflammation has garnered increasing attention, but studies in younger populations are limited. This study aimed to investigate the association between serum vitamin C and high-sensitivity C-reactive protein (hs-CRP) levels in children and adolescents. A cross-sectional analysis was conducted using data from the National Health and Nutrition Examination Survey (NHANES). The demographic data of 1766 participants aged 6–19 years were analyzed using t-tests and chi-square tests. The relationship between serum vitamin C and hs-CRP levels was analyzed using logistic regression, trend tests, and smooth curve fitting. Subgroup analyses and interaction tests were performed to assess the stability of the relationship across different populations. Our findings indicated a negative correlation between serum vitamin C and hs-CRP levels. In the fully adjusted model, each unit increase in serum vitamin C was associated with a reduction of 0.84 mg/L in hs-CRP levels (β = -0.84, 95% confidence interval [CI]: -1.34, -0.35). The hs-CRP levels in the vitamin C saturating group were 3.04 mg/L lower than those in the deficiency group (β = -3.04, 95% CI: -4.99, -1.08). This correlation was more significant in males, individuals with a family income to poverty ratio of ≤ 1.3, and those with a body mass index of ≥ 30 kg/m2. Serum vitamin C levels were negatively correlated with hs-CRP levels in American children and adolescents aged 6–19 years. Males, individuals from low-income families, and those who are overweight derived greater benefits from higher serum vitamin C concentrations.